Leibniz on Necessary and Contingent Truths - Muhit, Md Abdul (Arts Faculty Journal, 2012)
The distinction between necessary and contingent truths has so much important role in the explication of Leibnizs philosophy of logic, metaphysics, and philosophy of science that the distinction spreads throughout most of his philosophical writings. My aim in this paper is to try to provide a clear and detailed account of some of the aspects of Leibnizs distinction between necessary and contingent truths. This paper is divided into four parts. In the first part, an analysis of Leibnizs general notion of truth (the Principle of the Predicate-in-Notion) is given. This will be followed by his distinction between necessary truths and contingent truths, which he also terms as truths of reason and truths of fact respectively. Thirdly, the implication of this distinction in Leibnizs theory of human freedom will be addressed. I will end my discussion with an answer to the following questions: The distinction goes traditionally under Leibniz' name; but is it his own invention, or has he merely picked it up from one of his predecessors? And secondly, how far this distinction has an impact (if any) on the philosophies of his contemporaries, especially on Wolff, Hume and Kant? DOI: http://dx.doi.org/10.3329/afj.v4i0.12936 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.117-135